Golgi Phosphoprotein 73: The Driver of Epithelial-Mesenchymal Transition in Cancer - Liu, Yiming; Hu, Xinyang; Liu, Shiyao; Zhou, Sining; Chen, Zhi; Jin, Hongchuan (Frontiers in Oncology, 2021)
Golgi Phosphoprotein 73 (GP73, also termed as GOLM1 or GOLPH2) is a glycosylated protein residing on cis-Golgi cisternae and highly expressed in various types of cancer tissues. Since GP73 is a secretory protein and detectable in serum derived from cancer patients, it has been regarded as a novel serum biomarker for the diagnosis of different cancers, especially hepatocellular carcinoma (HCC). However, the functional roles of GP73 in cancer development are still poorly understood. In recent years, it has been discovered that GP73 acts as a multi-functional protein facilitating cancer progression, and strikingly, it has been identified as a leading factor promoting epithelial-mesenchymal transition (EMT) of cancer cells and causing cancer metastasis. In this review, we have overviewed the latest findings of the functional roles of GP73 in elevating cancer progression, especially in facilitating EMT and cancer metastasis through modulating expression, transactivation, and trafficking of EMT-related proteins. Besides, unsolved research fields of GP73 have been lightened, which might be helpful to elucidate the regulatory mechanisms of GP73 on EMT and provide potential approaches in therapeutics against cancer metastasis.